2005
DOI: 10.1007/s10517-006-0066-7
|View full text |Cite
|
Sign up to set email alerts
|

Level of liver fibrosis and immune status of mice of different age after heroin treatment and long abstinence

Abstract: Young and middle-aged CBA mice were injected with "street" heroin in increasing doses for 14 days. Volume density of perisinusoid argirophilic fibers increased in both age groups (the increase being more pronounced in middle-aged mice), while the levels of spontaneous, LPS- and ConA-stimulated splenocyte proliferation decreased in young mice. Six months after heroin discontinuation further progress of liver fibrosis was observed in young mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Cross‐sectional studies demonstrate that heroin users have higher transaminase levels compared with users of other drugs or alcohol [14] and increased collagen deposition compared with non‐drug users [15]. Other experimental studies have identified only a moderate effect of opioids on elevation of transaminase levels [16], glutathione levels [17] and fibrosis [18]. A cross‐sectional study of HCV‐infected male veterans failed to show an association between methadone use and liver fibrosis [19].…”
Section: Introductionmentioning
confidence: 99%
“…Cross‐sectional studies demonstrate that heroin users have higher transaminase levels compared with users of other drugs or alcohol [14] and increased collagen deposition compared with non‐drug users [15]. Other experimental studies have identified only a moderate effect of opioids on elevation of transaminase levels [16], glutathione levels [17] and fibrosis [18]. A cross‐sectional study of HCV‐infected male veterans failed to show an association between methadone use and liver fibrosis [19].…”
Section: Introductionmentioning
confidence: 99%